Faktor-Faktor yang Mempengaruhi Loyalitas Muzakki dan Kepercayaan Sebagai Mediasi di LazisMu Cabang Suruh Kabupaten Semarang - Mustofa, Nur Huri; Dwi Suci Rahayu (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2022)
Economic inequality in Indonesia is still relatively high as well as uneven welfare. Indonesia is a country where the majority of the population is Muslim. Besides that, Indonesia has several institutions that are devoted to empowering the community in reducing poverty, one of which is the LazisMu institution. There is still little awareness of the Muslim community to pay tithe in the LazisMu institution and there are still some people who do not understand the existence of the institution. By providing recommendations, information, and openness, the public can understand and be willing to donate to the institution. This study aims to determine the effect of word of mouth, transparency, and service quality of zakat management institutions on muzakki loyalty and muzakki trust as intervening variables. This type of research uses quantitative purposive sampling method, the sample used is 63 muzakki, data collected using a questionnaire processed with IBM SPSS 21. The results of this study indicate that Word of Mouth, Transparency, and Service Quality, have a significant positive effect on muzakki loyalty while the trust variable does not. significant positive effect on muzakki loyalty. And for the Intervening variable (Muzakki Trust) there is no mediating effect between Word of Mouth and Transparency on Muzakki Loyalty, but for service quality it has a mediating effect on Muzakki Loyalty.